Differences in Time of Birth between Spontaneous and Operative Vaginal Births - Hong, Christopher X.; Masteling, Mariana; Zhou, Clarice G.; Janssen, Matthew K.; Triebwasser, Jourdan E. (American Journal of Perinatology, 2024)
Previous studies have identified an association between obstetric interventions and the time of day in which they are performed; however, they do not account for granular variations in the temporality of delivery interventions, which is influenced by both health care providers and resource availability. We sought to assess differences in time of birth among spontaneous vaginal births (SVBs) versus operative (forceps- and vacuum-assisted) vaginal births (OVBs).This cross-sectional study used birth certificate data from the National Vital Statistics System from 2016 to 2021, which includes the time of birth and delivery method for recorded U.S. births. The number of SVBs and OVBs at each minute was normalized relative to the total births within each delivery group to facilitate balanced comparisons between groups. Logistic regression analysis assessed the odds of OVBs per time of day.A total of 15,412,129 subjects who underwent vaginal birth were included in this analysis, 690,905 (4.5%) of whom underwent OVBs. Compared to births at other time intervals, those between 4:30 and 7:30 p.m. were more likely to be OVBs (odds ratio [OR] = 1.13, 95% confidence interval [CI]: 1.12–1.14). Conversely, births between 3:00 and 6:00 a.m. were less likely to be OVBs (OR = 0.87, 95% CI: 0.86–0.88). After adjusting for adjusting for maternal age, gestational age, and induction of labor, births between 4:30 and 7:30 p.m. remained more likely to be OVBs (adjusted odds ratio [aOR] = 1.09, 95% CI: 1.08–1.10) and births between 3:00 and 6:00 a.m. remained less likely to be OVBs (aOR = 0.91, 95% CI: 0.90–0.92).In this population-based study, we identified temporal differences between SVBs and OVBs with increased use of instrumentation during the late afternoon and reduced use in the early morning. These findings prompt further investigation into the indications for OVBs and root causes of these temporal variations, which are likely multifactorial and involve provider and resource availability.
Keywords: obstetric interventions; temporal variations; operative vaginal births; birth timing